Using differentiation, show that f(x) = 2x^3 - 12x^2 + 25x - 11 is an increasing function.

First compute the derivative of f(x) using the power rule on each term. f(x) = 2x^3 - 12x^2 + 25x - 11 so f'(x) = 6x^2 - 24x + 25. Now complete the square for the derivative. f'(x) = 6 * ((x-2)^2 - 4) + 25 = 6 * (x-2)^2 - 24 + 25 = 6 * (x-2)^2 + 1. Now observe that the first term is >= 0 since it is the result of a square multiplied by the positive constant 6. The second term, 1, is positive. Hence the whole expression is positive for any x. So we've shown that f'(x) > 0 for any x, so the function f(x) is increasing.

Related Further Mathematics GCSE answers

All answers ▸

A circle has equation x^{2}-8x+y^{2}-6y=d. A line is tangent to this circle and passes through points A and B, (0,17) and (17,0) respectively. Find the radius of the circle.


The function f is given by f(x) = SQRT(2x − 5). Work out x when f(x) = 1.2


Work out the gradient of the curve y=x^3(x-3) at the point (3,17)


The equation of a curve is y = x^2 - 5x. Work out dy/dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences